Mind the Gap: The New Special Educational Needs and Disability Legislation in England - Castro, Susana; Palikara, Olympia (Frontiers in Education, 2016)
With the introduction of the Children and Families Act 2014, changes to the process of assessment and identification of children in need of special support in England and Wales have been introduced. These changes are regarded as the most significant in two decades, with consequent implications for service provision. In this paper we suggest that there is a gap between the theoretical approach to disability portrayed in the new policy, and many of the practical changes consequently introduced. To examine this mismatch, a sequence of arguments is presented, as a critical analysis of the approach introduced by the new policy, in light of a framework recognised worldwide for conceiving and classifying disability – the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY). Although the ICF-CY is not mentioned in the new policy for special educational needs and disability, possible links between the two are presented, with implications for service provision.